Tablet kunyah ekstrak etanol herba pegagan (Centella asiatica (L.), Urban) menurunkan kadar kreatinin tikus putih jantan (Rattus norvegicus L.) galur wistar yang diberi diet lemak tinggi - Akrom Akrom, Dr., dr., M.Kes; Nur Prasetyawan (Universitas Ahmad Dahlan, 2016)
A chewable tablet dosage ethanol extract of herb gotu kola (TKEEHP) has developed. Research to determine the impact of TKEEHP on kidney function has been conducted. Gotu kola herb is one of the medicinal plants that allegedly serves as antioxidative nefroprotektor. The purpose of this study is to assess the effect of TKEEHP on the changes in serum levels of creatinine and urea of male Wistar rats that had been given a high-fat diet. The experimental research was conducted on 21 Wistar rats aged 2-3 months (150-200 g body weight). Rats were divided into seven groups. Group I (normal) was given normal diet. Group II, III, IV, V, VI, and VII were given a high fat diet for 5 weeks. In the week 5 and 6 group III (positive control) was given SimvastatinÂ®, group IV was given placebo tablets, and the group V, VI and VII were given 100, 200 and 300 mg / KgBW TKEEHP, respectively. At the end of week 6 rats have blood drawn through orbital sinus and then tested serum levels of creatinine and urea.Data examination of urea and creatinine serum levels were analyzed with ANOVA) and LSD with confience interval of 95%. The results showed TKEEHP reduce the levels of creatinine in male Wistar rats given a high fat diet, but did not affect serum urea levels. TKEEHP with the dose of 100 mg / KgBW, 200 mg / KgBW, and 300 mg / KgBW show potency to lower creatinine levels and decrease serum creatinine levels at the highest dose of 300 mg / KgBW.